2022
DOI: 10.4103/amit.amit_27_22
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence as a Predictor of Work-Related Stress among Doctors

Abstract: Introduction: Workplace violence (WPV) toward health-care workers is increasing. The present study aims to estimate the proportion of resident doctors and interns of a tertiary care hospital who experienced WPV, to find out the perpetrators of WPV, and to ascertain any association between WPV and work-related stress. Materials and Methods: This observational, institution-based, cross-sectional study included resident doctors and interns working in six d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Workplace violence is one of the major sources of stress that leads to a variety of negative emotions [21]. Studies on healthcare workers found that those who had experienced workplace violence reported higher levels of stress [22,23],…”
Section: Introductionmentioning
confidence: 99%
“…Workplace violence is one of the major sources of stress that leads to a variety of negative emotions [21]. Studies on healthcare workers found that those who had experienced workplace violence reported higher levels of stress [22,23],…”
Section: Introductionmentioning
confidence: 99%